KEMUKJIZATAN PSIKOLOGI ALQURAN JAMAAH MAJELIS TAKLIM (Studi Kasus di Kecamatan Bogor Selatan Bogor) - Dwi Saputra, Ali Thaufan (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
The author?s main concern in this research is to study the miracles of Alquran and psychology of religion. Several theories in this study are used to see the contents of the soul and the Alquran reading of the members of three majelis taklim located in Bogor Selatan District, Bogor City. This research uses qualitative method and adopts the psychology approach. The bibliographic data (primary books on the miracles of Alquran and psychology) and field (interview, questionnaire) are used to analyze the psychological miracles of the majelis taklim members. Academically, this study can complement the existing books that discuss the miracles of Alquran. In terms of the science of Alquran, this study affirms the existence of miracles in Alquran, and the psychological effects on the reader. While psychologically, this study wants to show that the holy book - in any religion - is very important to its adherents. In the end, this study would like to prove that the the members of majelis taklim who read and hear the Alquran will feel the peace and tranquility of the soul. Furthermore, reading and listening to the Alquran will not only gives peace to the soul, but can increase faith and implicate the conduct of worshipers such as prayers and infak. The results of this study show that after reading the Alquran, the members of majelis taklim feel the calm. But the implications for an increase in faith involving congregational prayer and infak very fluctuational (unstable). It can be introduced that one?s faith can indeed increase and decrease (yazdâd wa yankus).